Análise dos contornos normativos das políticas educacionais implantadas pela SEED - PR durante a pandemia (2020-2021). - Niedermayer, Isabel Cristina (2023)
The object of study of this dissertation is the analysis of the normative contours of educational policies implemented by the State Department of Education and Sport of Paraná (SEED-PR) during the SARS-CoV-2 pandemic in the period 2020 and 2021. The research reveals a completely social historical context, which contributes to the analysis of the implementation of educational regulations in Paraná, through the following problem: the educational contours of Basic Education of SEED-PR, facing the need for social isolation in the pandemic, were adequate and fulfilled their role of ensuring the continuity of classes remotely and synchronously? From the problem presented, a bibliographical and documentary research was carried out, based on qualitative and quantitative, having as primary sources data already organized by official documents such as guidelines, resolutions, offices, instructions, ordinances, opinions, guidelines, notes, decrees, provisional measures, deliberations, laws, protocols, recommendations, indications and instructions, in order to continue the teaching activities in the public network of Paraná. The dialectical historical materialist method marks all this research, where it presents a historical dimension of social processes, providing the basis for an interpretation of the totality of reality. In this sense, the research went through three moments: the first is the contextualization and discussion of the policies of the former government of Jair Messias Bolsonaro and the government of Carlos Roberto Massa Júnior to confront the SARS-CoV-2 virus in Brazil and Paraná. The second moment is to examine neoliberal policies in the context of the SARS-CoV-2 pandemic, where the destruction of social rights and the precariousness of labor exposes the division of classes. Finally, we analyzed the normative contours implemented by SEED-PR, referring to the educational policy in the SARS-CoV-2 pandemic for the continuation of classes between 202 and 2021. It is concluded that the state of Paraná where its government aligned with the federal government of then, showed in its policies purposely against the emergence of the World Health Organization (WHO) to save lives in the context of a pandemic. It is known that the SARS-COV-2 pandemic suddenly unveiled a new reality present in the organization of society, and in school, it was no different. It was found that in order to continue the school calendar, the SEED-PR in line with the Ministry of Education and Culture (MEC), implemented in advance the non-classroom teaching, however this action did not take into account the social contexts, cultural and economic students.